Pengaruh Pendekatan Deep Learning Terhadap Kemampuan Pemecahan Masalah Matematika di Kelas XI SMK - sitanggang, suryani; Naibaho, Tutiarny; Panjaitan, Simon M. (Universitas PGRI Semarang, 2026)
This study was motivated by the low level of mathematical problem-solving skills among students at the Jambi Medan Private Vocational High School, which is attributed to the use of conventional teaching methods that do not sufficiently encourage active engagement and deep understanding. The objective of this study is to determine the influence and magnitude of the impact of the Deep Learning approach on the mathematical problem-solving skills of 11th-grade students in matrix material. The research method used is a Quasi-Experiment with a Post-test Only Control Group Design. The research population includes all 11th-grade students, with a sample selected through Cluster Random Sampling consisting of class XI MPLB 2 as the experimental class and XI MPLB 1 as the control class. Data analysis results showed that the average post-test score of the experimental class (72.62) was higher than that of the control class (46.40). Based on the t-test, a significance value of 0.000 0.05 was obtained, indicating a significant effect. The Effect Size test using Cohen’s D yielded a value of 3.29, which falls under the “very large” criterion. Thus, the Deep Learning approach is effective in improving students’ mathematical problem-solving skills at the Jambi Medan Private Vocational High School.